ALGORITHM FOR APPLICATION OF BAYES' THEOREM FOR DETECTION OF THREATS IN INFORMATION SECURITY SYSTEMS - Gluhov, Serhiy; Polovinkin, Igor; Kuzmenko, Maksym; Ponomarenko, Vitaly (Ukrainian Information Security Research Journal, 2024)
Information protection is becoming more relevant in today's world. This is due to the growth of technical progress and the transformation of the world into an information world. This became especially noticeable after the worldwide quarantine from the corona virus, humanity generally switched to information communication. Social networks and, in general, information communication through the worldwide network of Internet cyberspace have acquired further development. In connection with this, the scientific task of developing new and improving existing methods of information protection arises. One of the ways to improve information protection is the application of Bayes' theorem. The paper proposes the practical application of Bayes' theorem to increase the effectiveness of danger detection in the information protection and information security system of the State. Mathematical calculations proved the expediency of using Bayes' theorem to detect violations of confidentiality and truthfulness of information. According to the results of calculations using specific assumptions, we received a posteriori evidence in favor of the fact that the spectrum of the signal is the spectrum of the signal of a means of secretly obtaining information is about 33:1, and for determining false information, the a posteriori chance that the information is not false information is 10:1, that is are good results. In this way, it was proved that the use of Bayes' theorem to determine the security of information according to the proposed algorithm is an improvement of the method of assessing information protection and allows solving the scientific task of increasing the effectiveness of information protection and information security of the State.